Analysis of the use of soft systems methodology in theses in the Information Science field - Moraes, Cássia Regina Bassan de; Souza, Leonardo Pereira Pinheiro de (Informação em Pauta, 2020)
There is a large volume of work in Information Science addressing organizational context and complex social situations. These contexts, composed of heterogeneous elements, such as people, processes, cultures and the like, are difficult to understand using quantitative methods. Some Information Science researchers are using the Soft Systems Methodology to understand how information and knowledge systemically aggregate elements of these contexts, elucidating gaps and proposing solutions. This methodology is based on a dialog between subjects involved in the problematic situation for a holistic understanding of it. Being non-prescriptive, the methodology in question provides guidelines, but allows flexibility as to the mode and scope of application. Thus, it aims to investigate the use of the methodology aforementioned in theses of the Information Science programs best rated by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior, highlighting correlations in these works between the Soft Systems Methodology and various fields of Science Information. Therefore, the scope study method is used to perform a bibliographic mapping. As a result, it was found that the methodology considered is used in conjunction with the most diverse themes, both those focused on management, as well as more traditional ones, such as documentation, with a growth potential for their employment, as it adapts well to different types of research, especially those that consider reality as a complex social system.